Impact of the Coronavirus on Providing Oral Health Care in the Netherlands - Ilona F. Persoon; Catherine M.C. Volgenant; Monique H. van der Veen; Niek J.M. Opdam; David J. Manton; Josef J.M. Bruers (Elsevier, 2022)
Objective: Transmission of SARS-CoV-2 during oral health care is potentially increased compared to regular social activities. Specific amendments to the Dutch national infection control guidelines were promulgated. This study aimed to map the impact of the coronavirus pandemic on providing oral health care during the first wave of the coronavirus pandemic in 2020 in the Netherlands. Methods: A cross-sectional web-based survey was sent via email to a representative sample of dental hygienists and dentists in the Netherlands. Results: Of the 1700 oral health care practitioners approached, 440 (25.9%) responded to the survey. Patient access to oral health care was severely restricted during the lockdown in the spring of 2020. A total of 1.6% of the oral health care practitioners had laboratory-confirmed COVID-19 during the study period, although this is likely to be an underrepresentation due to limited access to testing at that time. Over half of the participants perceived an increased risk of virus transmission during aerosol-generating treatments in their practices. A large majority (65.0%-87.1%) of the oral health care practitioners followed the COVID-19-specific amendments to the national infection control guidelines. Compared to the pre-pandemic period, additional personal protective equipment and protocols were applied. Factors related with compliance with the additional recommendations were age, employment status, and occupation. Conclusions: The pandemic had a profound impact on both the accessibility and practice of oral health care. This survey study found that most Dutch oral health care practitioners paid extra attention to hygiene and infection control. Also, a low number of COVID-19 infections detected amongst Dutch oral health care practitioners was reported in the Netherlands. These overall outcomes suggest that safe oral health care can be provided when following the current infection control recommendations.